2019
DOI: 10.1016/j.abd.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Trend of leprosy detection rate in Brazil, 1990 to 2016

Abstract: The objective of this study was to describe the trend of detection of the disease in Brazil from 1990 to 2016. The joinpoint regression model was used. There was a significant trend of decreased detection in the country (average annual percent change  −1.8%) and in the South (average annual percent change = −3.5%) and Southeast regions (average annual percent change = −4.5%). The Northeast (average annual percent change = 0.2%), the Central-West (average annual percent change = −1.5%), and the North (average a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 4 publications
(3 reference statements)
3
16
0
Order By: Relevance
“… 13 , 37 , 38 Northeast, North, and Midwest regions present the highest prevalence rates and represent the poorest areas of the country. 37 , 39 , 40 …”
Section: Discussionmentioning
confidence: 99%
“… 13 , 37 , 38 Northeast, North, and Midwest regions present the highest prevalence rates and represent the poorest areas of the country. 37 , 39 , 40 …”
Section: Discussionmentioning
confidence: 99%
“…In Brazil specifically, 28,660 new cases were registered in 2018. Studies show that although there is a downward trend in the detection rate of new cases in the country over the past 10 years 5 , some changes in the epidemiological features, such as increased incidence among older people developing leprosy, were observed 6 , 7 , while some regions still show stagnant or increasing rates 8 . In particular, leprosy persists in the north and northeast regions as a critical public health problem 9 , 10 , demonstrating the heterogeneity of the epidemic in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, there was no significant reduction in the annual incidence rate, with detection rates still high, especially in states in the poorer regions of the North and Northeast. Corroborating that, a study conducted by Souza et al [7] demonstrated that despite the advances achieved in Brazil, the average detection rate in the period (1990–2016) was 22.13/100,000 inhabitants, classifying the country as very high endemicity for leprosy.…”
Section: Discussionmentioning
confidence: 94%
“…Leprosy is a neglected tropical disease. Due to cultural issues (such as stigma and fear of isolation) and the precariousness of health services, long delays of up to 10 years in the diagnosis of leprosy patients have been reported in many regions of Brazil [5,7]. In such circumstances, leprosy can progress to more severe forms (such as multibacillary – MB), which increases the risk of spreading the bacillus and maintains the transmission's cycle in endemic areas [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation